System of Government and Cross Death in the Ecuadorian Constitution of 2008: Revolution or Simple Reform? - Mora Varela, Jaime (2011)
This text presents a definition of the government system, within the political scheme and its complexities, trying to offer a classification of the different existing systems, pointing out their characteristics, strengths and weaknesses. This with the purpose of analyzing from a critical perspective the government system enshrined in the 2008 Constitution, making a balance, in terms of continuity or rupture, with respect to the presidential government system established by the 1998 Constitution.